Violet and Daisy : the story of vaudeville's famous conjoined twins - Miller, Sarah Elizabeth, 1979- (Schwartz & Wade Books, 2021)
Explores the lives of Daisy and Violet Hilton, conjoined twins born in 1908, abandoned by their mother, and placed on exhibition. Follows the girls as they travel from Brighton, England to Australian amusement parks and to American sideshows, where they eventually became famous on the vaudeville circuit. Also discusses who Violet and Daisy were as individuals and their lives after retiring from the stage.